The Legend of the Milled Well in Sendangduwur Village, Paciran District: Study of Narrative Structure, Cultural Values and Community Reception - Sutardi, Sutardi; Ihsan, Bisarul; PRADANA, YOGA AMAR (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
The legend of Sumur Giling is a famous oral story in Sendangduwur Village. This research focuses on narrative structure, cultural values, and community reception. This qualitative research uses Maranda's narrative structure theory, Koentjaraningrat's cultural value theory, and Nyoman Kunta Ratna's community reception theory. Data was collected through observation, interviews, recording, note-taking, transcription, transliteration and translation. Analysis shows that this story has a plot structure, characters and functions that are consistent with the values ​​of good, justice and evil. The cultural values ​​contained include belief in a creator, relationships between humans, and relationships with nature. People still attach importance to and believe in this legend, with elements such as the mosque appearing suddenly and the blessing of the milled well which is believed to be related to the Sunan Sendang karomah.